Development Of Gene Deleted Recombinant Pseudorabies Virus - Alauddin, Zeenathul Nazariah (2004)
The glycoprotein E (gE) and thymidine kinase (TK) genes are virulence-associated genes of pseudorabies virus (PrV). The study conducted was to shut down the gE gene from an established local TK defective (TK¯) PrV strain (TK¯gE+PrV). The ultimate aim of the study was to develop a gene-deleted recombinant PrV with useful identification markers. A gE gene-deleted pseudorabies virus (TK¯gE¯PrV) was constructed by homologous recombinational techniques. The TK¯gE+PrV, regarded as the parental strain in the study, originated from a virulent local PrV isolate (TK+gE+PrV). Prior to the construction of the TK¯gE¯PrV, the gE of the parental strain was amplified, cloned and studied. Comparative sequence analysis showed that the gE sequence of TK¯gE+PrV was closely identical (98 %) to a Chinese Ea strain. The 10 nucleotide variations at nucleotide positions 237, 931, 1207, 1409, 1501, 1530, 1549, 1555, 1682 and 1842, led to six amino acids substitutions at amino acid residues 403 (A